Aplikasi Sistem Antrian Pengadilan Agama Boyolali Sebagai Upaya Meningkatkan Pelayanan Umum Berbasis Web dan Android - Arif Trijoko; Dwi Kristiani; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2021)
The Office of the Boyolali Religious Court provides to each general public, consisting of seven types of services, namely complaint services, information, registration, registration, e-court corner, registration of power of attorney, and the collection of salput and divorce deed. In the queue system there is a problem which is where the officer first prepares the inventory of the queue number that has been printed and the counter operator calls the user orally, using a loudspeaker. The purpose of this research was to create a web-based queuing system for counter attendants in queue number calling, using the Codeigniter Framework and android-based applications for users to select and retrieve queue numbers, using Frame Work Flutter, the Dart programming language accessed offline using LAN (Local Area Network). The methods used in this study are the RAD (Rappid Application Development) method, modeling objects using UML and testing the system using blackbox. The result is a web and android-based queue system application to assist officers in printing queue numbers and counter operators in queue number calling.